1981
DOI: 10.1111/j.1600-0447.1981.tb00711.x
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐ and postsynaptic effects of zimelidine and norzimelidine on the serotoninergic system: single cell studies in the rat

Abstract: The pre-and postsynaptic effects of zimelidine and norzimelidine were studied in adult male Sprague-Dawley rats. The potency of the presynap tic effect was estimated from their ability to depress the rate of firing of serotonin (5-HT)-containing raphe neurons. Chronic administration of tricyclic antidepressant drugs has been shown to sensitize forebrain postsynaptic 5-HT receptors. The effect of zimelidine on these receptors was compared to that of saline and chlorimipramine by assessing the responsiveness of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

1981
1981
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(19 citation statements)
references
References 40 publications
(8 reference statements)
2
17
0
Order By: Relevance
“…The acute intravenous administration of 5-HT reuptake inhibitors suppresses the firing activity of the 5-HT neurons of the dorsal and median raphe nuclei (de Montigny et al 1981;Blier et al 1984;Chaput et al 1986;Hajós et al 1995) ACh-induced firing activity in control and in 5,7-DHT-lesioned rats is shown in B. * p Ͻ .01, compared to control values using the non-paired Student's t-test.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The acute intravenous administration of 5-HT reuptake inhibitors suppresses the firing activity of the 5-HT neurons of the dorsal and median raphe nuclei (de Montigny et al 1981;Blier et al 1984;Chaput et al 1986;Hajós et al 1995) ACh-induced firing activity in control and in 5,7-DHT-lesioned rats is shown in B. * p Ͻ .01, compared to control values using the non-paired Student's t-test.…”
Section: Discussionmentioning
confidence: 99%
“…The acute intravenous administration of 5-HT reuptake inhibitors suppresses the firing activity of the 5-HT neurons of the dorsal and median raphe nuclei (de Montigny et al 1981;Blier et al 1984;Chaput et al 1986;Hajós et al 1995) due to an enhanced activation of the somatodendritic 5-HT 1A autoreceptor by an increased level of extracellular 5-HT in the raphe (Adell and Artigas 1991;Bel and Artigas 1993;Hajós et al 1995;Gartside et al 1995;Rutter et al 1995;Béïque et al 1999). ACh-induced firing activity in control and in 5,7-DHT-lesioned rats is shown in B.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…41 Increasing 5-HT levels activates 5-HT 1A autoreceptors, resulting in less 5-HT being released into the synaptic cleft within minutes. 42 A higher 5-HT concentration increases activation of presynaptic 5-HT 1B autoreceptors, which alone can reduce the release of 5-HT. Under normal physiological conditions, the net effect of acute administration of SSRIs is little to no increase in 5-HT neurotransmission and minimal or no stimulation of postsynaptic 5-HT receptors.…”
Section: Antidepressive Agentsmentioning
confidence: 99%